Umbrella effects e a repressão a cartéis no Brasil: análise sob a ótica do private enforcement - Paulo Marcio Reis Santos (2019)
The institute umbrella effects, or price umbrella, can be considered one of thepossible consequences of the formation of cartels. Based on comparative lawstudies, with a special focus in the United States and the European Union, this thesisaims to investigate whether Brazilian law legitimizes civil liability against cartelmembers, when competing companies that are not part of the conspiracy takeadvantage of the existence of collusion and increase their prices to values abovethose that would be practiced under normal competitive conditions. In Brazil, there isan incipient trend towards the filing of lawsuits seeking civil reparation for thedamages resulting from the formation of cartels (private enforcement), especiallyafter the occurrence of convictions by CADE (public enforcement). Concerning claimsfor redress against cartel participants in cases of umbrella effects, the investigationwill demonstrate that there are divergent positions in the District Courts and the USCourts of Appeal, a country where antitrust redress lawsuits are more common thanother jurisdictions. There is also record of decisions in Canada, and a specific case iscurrently being considered by the Supreme Court of the country. The research willexamine the decision of the Court of Justice of the European Union (CJEU) in June2014 in the Kone case, which acknowledged the possibility that members of a cartel,based on the principle of effective competition rules and the right to full compensationTreaty on the Functioning of the European Union (TFEU), respond for damage InBrazil, there is still no record of lawsuits involving the issue. In the doctrinal aspect,the existence of studies at the post-graduate level stricto sensu about the subject isnot observed either. In the methodological aspect, the thesis has an interdisciplinarynature, using contents and institutes of Economic Law (with a focus on CompetitionLaw), Comparative Law, Constitutional Law, Civil Law (civil liability). As a theoreticalframework, the legal bases put forward by the Court of Justice of the European Unionin the judgment of the Kone case and, in relation to the causal link, the theory ofadequate causality, the application of which is recognized by the jurisprudence of theSuperior Court of Justice. It will be argued that, once the right to compensationagainst the participants of the cartel has been proven to be acceptable for damagesarising from umbrella effects, the Brazilian collectivity will face another significantdeterrent against the formation of cartels and that will honor the right to fullcompensation.